-3-2=-2.5+1.4+8.6x

Math
-3-2=-2.5+1.4+8.6x
Rewrite the equation as -2.5+1.4+8.6x=-3-2.
-2.5+1.4+8.6x=-3-2
Add -2.5 and 1.4.
-1.1+8.6x=-3-2
Subtract 2 from -3.
-1.1+8.6x=-5
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Add 1.1 to both sides of the equation.
8.6x=-5+1.1
Add -5 and 1.1.
8.6x=-3.9
8.6x=-3.9
Divide each term by 8.6 and simplify.
Tap for more steps…
Divide each term in 8.6x=-3.9 by 8.6.
8.6×8.6=-3.98.6
Cancel the common factor of 8.6.
x=-3.98.6
Divide -3.9 by 8.6.
x=-0.45348837
x=-0.45348837
-3-2=-2.5+1.4+8.6x

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top